Konsep Kafaah Pernikahan Islam Dalam Adat Jawa - ulum, m wildanul (LPPM UNU BLITAR, 2024)
The concept of kafaah in Islamic marriage refers to equality or equality between the prospective bride and groom in various aspects such as religion, social status, economics and moral values. In the Javanese traditional context, this concept has a unique adaptation because marriage is not only seen as an individual bond, but also as a union between families and communities. In Javanese tradition, aspects of family harmony and harmony between social groups have a significant role. Kafaah in traditional Javanese weddings does not only focus on religious compatibility or socio-economic status, but also includes cultural values ​​such as courtesy, etiquette and respect for ancestors. Even so, there is a meeting point between the principle of kafaah in Islam and Javanese custom, namely emphasizing the importance of harmony to maintain harmony and sustainability of relationships in the household and community. This research aims to understand how the concept of kafaah is applied in Javanese traditional marriages and how these two values ​​interact with each other in social practice.